Pengamatan Bakteri pada Tanaman Asam Rebung Dendrocalamus Asper - Milla Astari; Ardi Mustakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Microorganisms are microscopic organisms that cannot be observed directly without the aid of optical instruments. They play an important role in various biological and environmental processes, both beneficial and detrimental. Most microorganisms are unicellular, but some are multicellular. Some microorganisms are also known to have benefits in the fields of food and health. Bamboo shoots or young bamboo are one type of vegetable that is widely consumed by the community, especially in Central Java. Bamboo shoots have a low nutritional content such as water, protein, carbohydrates, minerals, and fat, making them a healthy low-calorie food. In addition, bamboo shoots also contain bioactive compounds such as vitamins, essential amino acids, and antioxidants that are beneficial for body health.Fermentation of bamboo shoots is one method to increase their nutritional value and probiotic content.